The ways and methods of creation and upgrading of motion’s simulation means and aviation trainers in Ukraine - Азарсков, В. Н. (Proceedings of National Aviation University (archive), 1999)
Formulated is a global program and the series of particular science, research and engineering programs of creation (upgrading) in Ukraine of flight simulation systems and trainers. The ways and stages of aforementioned problems’ successful solution based on the usage of non-traditional approaches, tested at the complicated patterns of aerospace equipment are discussed